Pemberdayaan Masyarakat Melalui Pelatihan Pengolahan Air Kelapa Menjadi Nata De Coco Terfortifikasi Kitosan di Kelurahan Tiroang, Kabupaten Pinrang, Sulawesi Selatan - Natsir, Hasnah; Arif, Abdur Rahman; Arfah, Rugaiyah A; Budi, Prastawa; Zakir, Muhammad; Karim, Abdul; Fauziah, St; Nadir, Muhammad; Mardianti, Riska (Jurnal Pengabdian Masyarakat Borneo, 2024)
Coconut, particularly coconut water, serves many purposes in people's lives. Coconut water is generally consumed with the young fruit, but old coconut water is frequently discarded into the environment. Therefore, integrating coconut water into a product has a high economic value. The aims of this community service is to process coconut water into nata de coco by empowering the community through training for PKK members. This program's methodology included partner problem analysis and the available problem-solving strategy, which consists of counselling, training, and collecting data. The implementation of this activity resulted in numerous benefits, particularly increased public understanding of the role of coconut water in daily life, such as its nutritional value, processed products such as nata de coco, and other advantages. Based on the data collected, it is known that all participants have differing levels of knowledge about nata de coco products, namely 10% of participants know very well, 30% of participants know, and 12% of participants know little. However, 58% of participants were totally ignorant that coconut water is the starting material in nata de coco. Following the training, all participants understood that coconut water was the raw material in nata de coco. On the other hands, 75% of the participants were very understanding, 20% were quite understanding, and only 5% had a basic understanding of how to make nata de coco. These findings indicate that the solution of the activities carried out is extremely effective in increasing the participants' understanding and interest in making nata de coco, which can encourage the creation of "home industry" based jobs in the community, particularly in Tiroang Village.Â